EFFECT OF CUSTOMER VALUE AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION AND LOYALTY PT MERATUS SAMARINDA - Hasfar M; Theresia Militina; Gusti Norlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the effect of customer value and customer experience to customer satisfaction and loyalty PT Meratus. The population in this study are customers of PT Meratus by the number of 80 customers. Methods of data collection is done by providing a list of questions or the questionnaire respondents who are customers of PT Meratus, where questionnaires were distributed to such subscribers. This study uses data analysis tool which Partial Least Square (PLS), then this study using structural equation modeling analysis method or path analysis to determine the causal relationship between the latent variables contained in the structural equation. While testing the hypothesis tested boost strap resampling method developed by Geisser and Stone. Statistical test used statistical test t or t test, with statistical hypothesis. The tools used in processing the data using PLS Smart program. The results of this study indicate that 1) customer experience influence positive and significant to customer satisfaction, 2)) customer experience influence positive and significant customer loyalty, 3) customer value effect on positive and significant to customer satisfaction, 4) customer value effect positive but are not with significant customer loyalty, 5) customer satisfaction and significant positive effect on customer loyalty.